2018
DOI: 10.15517/rbt.v66i3.30825
|View full text |Cite
|
Sign up to set email alerts
|

Effects of land use and limnological variables on the dissimilarity of common and rare aquatic insects in Atlantic Forest streams

Abstract: Lotic ecosystems are altered at various spatial scales leading to the simplification of water bodies and the dominance or exclusion of certain organisms. In streams, species may have limitations generated by the environment that result in a more abundant or rare occurrence. Thus, the aim of this study was to evaluate the influence of water physical-chemical variables and land use in the drainage basin on the composition of Ephemeroptera, Plecoptera and Trichoptera (EPT) assemblages in the streams of Atlantic F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
(45 reference statements)
1
7
0
Order By: Relevance
“…For the total macroinvertebrate assemblage, the partial Mantel tests detected stronger associations between environmental and compositional dissimilarities rather than geographic distances. In general, our results agree with those of previous authors that found that environmental conditions can play a major role rather than spatial distance in structuring the composition of stream macroinvertebrates (Astorga et al, 2012; Brown & Swan, 2010; Cañedo‐Argüelles et al, 2015; Maloney & Munguia, 2011; Ongaratto et al, 2018). In fact, reviews on the metacommunity organization of stream macroinvertebrates stress that environmental conditions are the main drivers of their composition, while spatial structure accounted by dispersal limitation can be related to specific features of the study region (Brown et al, 2011; Brown & Swan, 2010; Heino et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…For the total macroinvertebrate assemblage, the partial Mantel tests detected stronger associations between environmental and compositional dissimilarities rather than geographic distances. In general, our results agree with those of previous authors that found that environmental conditions can play a major role rather than spatial distance in structuring the composition of stream macroinvertebrates (Astorga et al, 2012; Brown & Swan, 2010; Cañedo‐Argüelles et al, 2015; Maloney & Munguia, 2011; Ongaratto et al, 2018). In fact, reviews on the metacommunity organization of stream macroinvertebrates stress that environmental conditions are the main drivers of their composition, while spatial structure accounted by dispersal limitation can be related to specific features of the study region (Brown et al, 2011; Brown & Swan, 2010; Heino et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…The composition of Chironomidae and Ephemeroptera larvae is highly responsive to local environmental conditions. Several studies conducted in southern Brazil showed that water quality (pH, EC), land use and substrate type are important drivers of composition of their assemblages (Floss, Kotzian, & Spies, 2012;Ongaratto et al, 2018;Salvarrey, Kotzian, Spies, & Braun, 2014). In addition, adult Chironomidae have an active flight in the adult stage, and overland dispersal can occur through wind (Johnson, 1969).…”
Section: Influence Of Environmental Dissimilarity and Geographic DImentioning
confidence: 99%
See 1 more Smart Citation
“…The pH was an important filter of the structure of the EPT community, and gradients of this variable are known to be an important factor determining the formation of the communities of other groups of aquatic insects (Brasil et al 2018, Ongaratto et al 2018, Ridl et al 2018. Gradients in the pH of the water have been associated with alterations in rainfall patterns, which may change the amount of dissolved solid matter added to the water, which is also dependent on the conditions in the area surrounding the stream (Pérez 2003, Juen et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Environmental assessment of aquatic invertebrate responses to anthropogenic disturbance helps to understand which factors drive community structure changes (Hepp et al, 2016;Castro, Dolédec, & Callisto, 2018;Ongaratto, Loureiro, Restello, & Hepp, 2018). Aquatic ecosystems in subtropical Brazil are presently under intense environmental pressure due to riparian vegetation suppression and allochthonous inputs from watercourses' surroundings (Ferreira, Cyrino, Duarte-Neto, & Martinelli, 2012).…”
mentioning
confidence: 99%